Linking ecosystem service benefit and grazing prohibition intensity can better optimize fence layout in northern Tibet. (15th January 2023) - Chen, Junhe; Wang, Yafeng; Sun, Jian; Zhang, Jianxiang; Zhang, Jingtian; Wang, Yingxin; Zhou, Tiancai; Huo, Huangyu; Liang, Eryuan
Abstract: There is an urgent need to link grazing exclusion policy and the resulting benefits for fence layout management. However, policy implementation intensity and benefits are rarely considered together. Here, combining the changes in the rate of the livestock and fenced area, we constructed a grazing prohibition intensity (GPI) index that reflected the intensity of policy implementation. We also quantified ecosystem service benefits (ESBs), including net primary productivity (NPP) and soil conservation by the different models. Then, a new perspective in combination with ESBs and GPI was used to assess whether a fence layout is appropriate using the four–quadrant model and how to optimize a potentially unreasonable fence layout based on seven drivers. We found that the NPP and soil conservation service notably increased by 59% and 87%, respectively, in the total fenced area, after the implementation of the grazing exclusion program. The high values of ESBs and GPI were concentrated in the eastern and central‐eastern regions of the northern Tibet, respectively. Moreover, the potentially unreasonable fence layout accounted for 10% of the total fenced area, and was focused on meadow areas with a high human footprint. The area proportion of reasonable fence layout coupling ESBs and GPI increased by 20% compared with ESBs individually. Finally, an optimal potential unreasonable fence layout might reduce the mismatch between the ESB and GPI by considering countermeasures such as attention to the potential unreasonable fence layout, setting a target for supplying carbon sinks and soil and water conservation quantities and reducing the human footprint. Our study indicates the necessity of linking ESBs and GPI for fence layout management.